Romanian Symbols Decodings and Interpretations - Mihaela Samoil-Cozma (Anastasis: Research in Medieval Culture and Art)
Book review: Loredana Gașpar, Simboluri românești decodificări și interpretări / Romanian Symbols Decodings and Interpretations, Performantica Publishing House, Iași, 2022, 362 pages.